Follow-up results of myositis patients treated with H. P. Acthar gel. (11th March 2020) - Saygin, Didem; Oddis, Chester V; Marder, Galina; Moghadam-Kia, Siamak; Nandkumar, Preeya; Neiman, Nicole; Dzanko, Sedin; Koontz, Diane; Aggarwal, Rohit
Abstract: Objectives: Idiopathic inflammatory myopathies (IIM) are a group of autoimmune diseases characterized by proximal muscle weakness. H. P. Acthar gel [repository corticotropin injection (RCI)] is a formulation of adrenocorticotropic hormone and has been approved by Food and Drug Administration for use in IIM; however, literature is limited. In this study, we report longitudinal follow-up of myositis patients treated with RCI. Methods: Patients with refractory IIM who were enrolled in the prospective, open-label RCI trial were included in this study. The post-trial follow-up period was 6 months with assessments every 2 months, which included myositis core set measures including extra-muscular global, muscle and patient global disease activities, HAQ, and manual muscle testing. Results: Two patients were lost to follow-up after finalization of the trial, and the remaining eight patients were enrolled in the follow-up study. One patient remained on RCI after the trial. In the follow-up period, four of eight patients had flare at on average 4.1 months after the RCI trial. Among the patients who flared, three required an increase in prednisone. One patient was restarted on RCI at 5.5 months, but had minimal improvement after 3 months. Four patients who remained stable continued to satisfy criteria for the definition of improvement through the 6-month follow-up. However, none showed any further improvement in the primary or secondary efficacy outcomes after the initial RCI trial. Conclusion: To our knowledge, this is the first study reporting the follow-up results of patients treated with standard dose and duration of Acthar. We believe that our study will provide the basis for the development of future randomized RCI trials in IIM.